Epistemology of the Self of Edgar Morin (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2020)
This research aims to surveying at the sight of the French philosopher Edgar Morin from the humane self in case which were agree to naming it at " Epistemology of the Complex" which aims to use the complex or the composite think considering it as an ideal agent in their studying and treating the things and phenomenon whether were natural or psychic or social by trying to confirm a perfect knowledge about it as a vicarious which what was known by the simple or abbreviated think. If the simple think aims to form a denudated, abbreviated and divided knowledge about the self by isolated it from its sequence and their conditions and relations by trying to tear the texture which it to belong with overall the things surrounded by it, and then trying to define this knowledge and coin it as a system of ideas and theories with a view to attain to a complete knowledge about the self. Whereas against that, the composite think aims to recoin and forming our information about the humane self by recombine it with the whole components surrounding by it until it becomes one correlate texture from the sides and the ends but not for defining of denudating it in this components may for showing its uniqueness firstly, secondly for its multiplicity, and thirdly for its impossibility from a complete knowledge of it. يعنى هذا البحث بالوقوف على رؤية الفيلسوف الفرنسي إدغار موران للذات الإنسانية في إطار ما اصطلح على تسميته بــ "أبستمولوجيا التعقيد" التي تسعى لاستخدام الفكر المركب أو المعقد، بوصفه الأداة المُثلى في دراستها ومعالجتها للأشياء والظواهر -سواء أكانت طبيعية أم نفسية أم اجتماعية- محاولة تكوين معرفة حقة عنها، وذلك كبديل عما يُعرف بالفكر البسيط أو الأختزالي. فإذا كان الفكر البسيط يسعى إلى تكوين معرفة مجزأة ومجردة ومختزلة عن الذات من خلال عزلها عن سياقها وشروطها وارتباطاتها، محاولاً تمزيق النسيج الذي تنخرط فيه مع مجمل ما يحيط بها، ومن ثم محاولة تأطير هذه المعرفة، وصياغتها على شكل نسق من الأفكار والنظريات بغية الوصول إلى معرفة مكتملة عن الذات، فإن الفكر المركب في مقابل ذلك يهدف إلى إعادة صياغة وتشكيل معرفتنا عن الذات الإنسانية عبر إعادة إدماجها بمجمل العناصر المحيطة بها، لتغدو نسيجاً واحداً مترابط الجوانب والأطراف، ولكن ليس بغرض تأطيرها أو اختزالها في هذه العناصر، وإنما لإظهار تميزها أولاً، وتعدديتها ثانياً، وتعذر تكوين معرفة ناجزة ومكتملة عنها ثالثاً.